Assessing Quality of Life Following Radical Cystectomy and Ileal Conduit for Bladder Cancer: A Study Utilizing EuroQol 5-Dimensional 3-Level - Richha Prabhakar; Rajat Prabhakar; Dharmapuri R. Rao (Journal of Marine Medical Society)
Background: Urinary bladder cancer continues to be a significant health challenge and often requires radical cystectomy with ileal conduit (RCIC) as a primary therapeutic intervention in Stage II/III disease. The impact of this surgery on patients’ quality of life (QoL) is a critical aspect of evaluating the overall success of bladder cancer management. Therefore, we conducted a study to assess patients’ QoL following RCIC in bladder cancer patients using EuroQol 5-dimensional 3-level (EQ-5D-3L) instrument. Materials and Methods: In this cross-sectional study, patients of urinary bladder cancers from tertiary care centers, who underwent RCIC as a part of their curative treatment, were evaluated 1 month following surgery for QoL using the EQ-5D-3L instrument, in which patients were asked to report problems in 5 dimensions of this questionnaire. Results: We found that RCIC has a substantial immediate negative impact on QoL, primarily due to postoperative discomfort, anxiety/depression, and other urinary diversion-related issues. Nearly 36% of patients had some or extreme problems in 3 or more dimensions out of 5 in EQ-5D-3L. Conclusion: This study highlights the significance of EQ-5D-3L as a tool for evaluating QoL in patients of bladder cancer following RCIC, providing a useful framework for comprehending the multidimensional nature of their experiences. The findings emphasize that to maximize QoL, bladder cancer treatment requires individualized interventions, psychosocial support, and collaborative decision-making in bladder cancer management.